2006
DOI: 10.1007/s11908-006-0061-1
|View full text |Cite
|
Sign up to set email alerts
|

The role of interventional pulmonary procedures in the management of post-obstructive pneumonia

Abstract: Post-obstructive pneumonia is the result of airway obstruction, commonly due to lung cancer. The majority of patients with lung cancer are non-operable and incurable at initial presentation. The clinical course of these patients is steadily downhill with complicating events such as post-obstructive pneumonia, respiratory failure, pleural effusion, and severe debilitation. Non-invasive conventional options for post-obstructive pneumonia include broad-spectrum antibiotics, combined with attempts at relieving the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…Post-obstructive pneumonia is difficult to treat with antibiotics alone because of poor drainage, and can lead to recurrent hospitalization, increased medical costs, and poor outcomes [1]. Actual incidence and cause of obstructive pneumonia has not been well elucidated; however, lung cancer has been considered as the most common cause of post-obstructive pneumonia, occurring in approximately 20% of the patients with proximal airway obstruction [1].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Post-obstructive pneumonia is difficult to treat with antibiotics alone because of poor drainage, and can lead to recurrent hospitalization, increased medical costs, and poor outcomes [1]. Actual incidence and cause of obstructive pneumonia has not been well elucidated; however, lung cancer has been considered as the most common cause of post-obstructive pneumonia, occurring in approximately 20% of the patients with proximal airway obstruction [1].…”
Section: Discussionmentioning
confidence: 99%
“…Actual incidence and cause of obstructive pneumonia has not been well elucidated; however, lung cancer has been considered as the most common cause of post-obstructive pneumonia, occurring in approximately 20% of the patients with proximal airway obstruction [1]. Benign diseases (e.g., foreign bodies, benign tumors, granulomatous diseases such as tuberculosis, or broncholithiasis) can obstruct the airways and induce post-obstructive pneumonia [15]. Jhun et al reported that 31% of the patients with benign endobronchial tumors exhibited obstructive pneumonia on chest CT scan [3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies were largely performed in COPD patients or perioperative patients undergoing pulmonary resection for cancer and additional studies are needed to see whether these results correlate with that found in postobstructive pneumonias. 27,28 In patients who cannot tolerate bronchoscopy alternate imaging is required. 26 The ability to sample a pulmonary lesion directly could be a significant advantage when sputum cultures are negative and the addition of endobronchial ultrasound has greatly enhanced the diagnostic utility of bronchoscopies.…”
Section: Role Of Bronchoscopymentioning
confidence: 99%
“…28 Bronchoplasty and airway stenting are also commonly used to restore airway patency with good results but also carry inherent risks. Interventional bronchoscopy techniques, such as tumor debulking with Nd:YAG laser have shown promise for the treatment of proximal airway lesions while argon plasma anticoagulation and electrocautery have also been used safely and effectively for removal of airway lesions while providing good hemostasis.…”
Section: Role Of Bronchoscopymentioning
confidence: 99%